Research progress on the mechanism of TCM regulating intestinal microbiota in the treatment of DM mellitus - Ping, Yang; Liu, Jianing; Wang, Lihong; Qiu, Hongbin; Zhang, Yu (Frontiers in Endocrinology, 2024)
In recent years, with the improvement of people's living standards, the incidence of DM has increased year by year in China. DM is a common metabolic syndrome characterized by hyperglycemia caused by genetic, environmental and other factors.At the same time, long-term suffering from DM will also have an impact on the heart, blood vessels, eyes, kidneys and nerves, and associated serious diseases. The human body has a large and complex gut microbiota, which has a significant impact on the body's metabolism. Research shows that the occurrence and development of DM and its complications are closely related to intestinal microbiota. At present, western medicine generally treats DM with drugs. The hypoglycemic effect is fast and strong, but it can have a series of side effects on the human body. Compared with western medicine, Chinese medicine has its unique views and methods in treating DM. TCM can improve symptoms and treat complications by improving the imbalance of microbiota in patients with DM. Its characteristics of health, safety, and reliability are widely accepted by the general public. This article reviews the relationship between intestinal microbiota and DM, as well as the mechanism of TCM intervention in DM by regulating intestinal microbiota.